A new species of the genus Bembecia Hübner, 1819 (Lepidoptera, Sesiidae) from Omsk Region of Russia (West Siberia) - Svyatoslav A. Knyazev (Acta Biologica Sibirica)
A new species, Bembecia lavrovi Knyazev, sp. n. from Omsk Region of Russia in West Siberia, is described based on a series of 80 specimens. A detailed description of the external characteristics of the male and female, as well as the structure of the male genitalia, is provided. The new species is close to Bembecia sareptana (Bartel, 1912) and Bembecia aktashica O. Gorbunov 2018 but is distinguished by its large size, more contrasting and bright coloring, details of the wing pattern and the structure of the genitals.